TEACHER PERFORMANCE DURING THE COVID-19 PANDEMIC - Tanthowi JAUHARI (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2022)
This study aims to determine the performance of teachers during the Covid-19 pandemic in public elementary schools in South Tangerang City in the aspects of planning lessons, implementing lessons, and assessing or evaluating learning. This study used a mixed method with a quantitative-qualitative approach. The research participants were 65 teachers. Data collection techniques through questionnaires, observation, and interviews. Data analysis technique is done by percentage test. Checking techniques and data validity using source and technique optimization. The results showed that teacher performance during the pandemic was obtained with a percentage value of 72.75% for the aspect of planning learning 79.85% for the aspect of carrying out learning, and the aspect of assessing learning obtained a value of 69.54%. The three aspects of planning, implementing, and assessing teacher learning are categorized as moderate or good enough. To improve teacher performance during this pandemic, teachers need to implement strategies such as increasing innovation and creativity during learning. This is done to reduce student boredom before learning begins, such as providing interesting videos so students will be more enthusiastic.